Rancang Bangun Sistem Exhaust Fan Otomatis Berbasis Sensor DHT11 dan Mikrokontroler ESP32 untuk Peningkatan Kualitas Udara di Smoking Area - Rifky Irfani; Achmad Aziz Rahmanto; Muhammad Edgar Gazazanata (Proklamasi 45 University, 2025)
Air pollution in smoking areas can significantly impact human health and reduce indoor air quality. Poor ventilation systems often fail to respond to real-time environmental changes, leading to increased exposure to harmful particles. This research develops an automatic exhaust fan system utilizing a DHT11 sensor and an ESP32 microcontroller to optimize air circulation. The system activates when the temperature exceeds 27°C or humidity surpasses 60%, ensuring effective ventilation control. The study employs a prototyping approach consisting of system design, hardware and software implementation, and performance testing. Results indicate a 20% reduction in energy consumption compared to manual operation, highlighting the system's efficiency. The DHT11 sensor records a temperature deviation of ±0.5°C and a humidity accuracy of ±2%, confirming its reliability. This system not only improves air quality but also supports energy efficiency, making it a viable solution for enclosed smoking areas in public spaces.